Application of an optimized interpretation model in capillary hemoglobin electrophoresis for newborn thalassemia screening. (10th September 2021) - Zou, Jie; Huang, Shuodan; Xi, Hui; Huang, Cidan; Zou, Lin; Qiu, Li; Nie, Xinghui; Zhou, Jin; Zhuang, Yuchang; Chen, Yajun; Xie, Longxu; Liu, Nansong; et al.
Abstract: Introduction: Newborn screening is an important supplement to thalassemia control and prevention. Capillary electrophoresis (CE) technology has several advantages for thalassemia screening but with low sensitivity, especially for thalassemia carriers. This study aims to illustrate the application of an optimized interpretation model in newborn thalassemia screening by capillary hemoglobin electrophoresis. Methods: Two thousand, two hundred fifty‐eight neonates selected from four regions in China were enrolled and were screened for α‐thalassemia and β‐thalassemia by capillary electrophoresis. Results were interpreted based on an optimized model integrated with multiple parameters. Molecular analysis was carried out in synchrony and used as the gold standard for the screening performance assessment. The consistency among different regions and thalassemia genotypes were also investigated. Results: Among the 2258 neonates, 485 were identified to have a likely diagnosis of thalassemia, and 422 α‐thalassemia, 80 β‐thalassemia, and 21 α/β‐thalassemia cases were confirmed by molecular analysis, including 277 α‐thalassemia silent carriers, 135 α‐thalassemia trait carriers, 10 Hemoglobin H disease, and 80 β‐thalassemia trait carriers. The screening sensitivity, specificity, positive, and negative predictive value for α‐thalassemia and β‐thalassemia were 84.83%, 99.14%, 95.98%, 96.41%, and 88.75%, 98.73%, 76.34%, and 99.48%, respectively. The optimized interpretation model showed higher performance for thalassemia carriers, though some neonates with silent α‐thalassemia genotypes (‐α 3.7 /αα, ‐α 4.2 /αα, and α WS α/αα) and β ‐28 /β N genotype were still missed. The screening performance among different regions was comparable. Conclusions: Capillary hemoglobin electrophoresis with the optimized interpretation model shows reliable performance for newborn thalassemia screening. It is applicable to large‐scale population screening.